A multifunctional environmentally friendly coating and preparation method thereof

By modifying MXene nanosheets and grafting polylysine, and compounding with Ce-MOF, an antibacterial and anticorrosive nanocomposite is formed, which solves the problem of insufficient performance of water-based polyurethane coatings and significantly improves its strength, corrosion resistance, and antibacterial properties. effectiveness and thermal stability.

CN118048102BActive Publication Date: 2025-01-21GANSU JINHONGQIAO GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410173667.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-07
Publication Date
2025-01-21
Estimated Expiration
2044-02-07

AI Technical Summary

Technical Problem

The fire-resistant, physical and mechanical properties of water-based polyurethane coatings are poor, and have single functions, which limits its application range.

Method used

Through (3-amino propyl) triabilite Silicine modifiers MXENE nanos tablets, then branches of polymealine to prepare MXENE nanos tablets/polyinninine composite materials, and compound with CE-MOF to form antibacterial anticorrosive corrosion Nano -composite materials are added to water -based polyurethane coatings.

Benefits of technology

It improves the strength, corrosion resistance, antibacterial effect and thermal stability of water-based polyurethane coatings, and enhances its physical and mechanical properties and fire resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118048102B_ABST
    Figure CN118048102B_ABST
Patent Text Reader

Abstract

This invention discloses a multifunctional environmentally friendly coating and its preparation method. The multifunctional environmentally friendly coating comprises the following components in parts by weight: 50-60 parts of waterborne polyurethane resin, 8-12 parts of antibacterial and anti-corrosion nanocomposite material, 2-5 parts of dispersant, 2-4 parts of defoamer, 2-4 parts of leveling agent, 2-4 parts of thickener, 1-3 parts of film-forming aid, and 15-25 parts of deionized water. This invention prepares an MXene nanosheet / polylysine composite material by modifying MXene nanosheets with (3-aminopropyl)triethoxysilane and then grafting polylysine onto them. Simultaneously, an antibacterial and anti-corrosion nanocomposite material obtained by compounding Ce-MOF is added to the waterborne polyurethane coating, thereby improving the strength, corrosion resistance, antibacterial effect, and thermal stability of the waterborne polyurethane coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and specifically relates to a multifunctional environmentally friendly coating and a preparation method thereof. Background Art

[0002] Paint is usually a viscous liquid made of resin, oil, or emulsion, with or without pigments, fillers, and corresponding additives, and is prepared with organic solvents or water. It can be applied to the surface of an object through different construction processes to form a solid film that is firmly adhered, has a certain strength, and is continuous. The coating film formed belongs to the type of polymer compounds. Modern paints tend to be synthetic, modified, and multifunctional engineering materials. Their main functions are to protect, decorate, enhance, and enhance the value of products.

[0003] Waterborne polyurethane coating is an environmentally friendly water-based coating that is non-toxic, does not pollute the environment, and has high hardness. Compared with traditional solvent-based polyurethane coatings, it has the characteristics of environmentally friendly production process, does not require a large amount of organic solvents, and has low VOC release. It is mainly used in automotive coatings, metal corrosion protection, furniture coatings and other fields. However, waterborne polyurethane has poor fire resistance and physical and mechanical properties, and its function is single, which to a certain extent limits the application of waterborne polyurethane.

[0004] The existing technologies currently have the following main problems: waterborne polyurethane coatings have poor fire retardancy and physical and mechanical properties and are single in function. Summary of the invention

[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a multifunctional environmentally friendly coating and a preparation method thereof. In order to solve the problems that the fire resistance and physical and mechanical properties of waterborne polyurethane coatings are poor and the functions are single, the present invention modifies MXene nanosheets by (3-aminopropyl) triethoxysilane, and then grafts polylysine to prepare MXene nanosheets / polylysine composite materials. At the same time, Ce-MOF is compounded to obtain an antibacterial and anticorrosive nanocomposite material, which is added to the waterborne polyurethane coating to improve the strength, corrosion resistance, antibacterial effect and thermal stability of the waterborne polyurethane coating.

[0006] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is as follows: The present invention proposes a multifunctional environmentally friendly coating and a preparation method thereof, wherein the multifunctional environmentally friendly coating comprises the following components in parts by weight: 50-60 parts of waterborne polyurethane resin, 8-12 parts of antibacterial and anticorrosive nanocomposite materials, 2-5 parts of dispersant, 2-4 parts of defoaming agent, 2-4 parts of leveling agent, 2-4 parts of thickener, 1-3 parts of film-forming aid, and 15-25 parts of deionized water.

[0007] Furthermore, the preparation method of the antibacterial and anticorrosive nanocomposite material comprises the following steps:

[0008] (1) Disperse LiF in 50 mL of HCl solution, add Ti3AlC2, and react at 35 °C with stirring for 24 h. After reaction, wash with deionized water until neutral, ultrasonicate for 40-60 min, centrifuge for 1-2 h, and dry the centrifuged product in an oven at 40 °C for 10-12 h to obtain MXene nanosheets.

[0009] (2) 1-2 g of the MXene nanosheet obtained in step (1) was added to a container containing 30 mL of ethanol aqueous solution, and ultrasonically treated for 30 min. 2-3 mL of triethylamine was added dropwise, and stirred at room temperature for 3-4 h. Then 2-3 mL of (3-aminopropyl)triethoxysilane was dissolved in 10 mL of ethanol and added to the above container. The mixture was reacted at 60 ° C for 8 h, washed with deionized water for 3 times, and vacuum dried at 60 ° C for 10 h to obtain modified MXene nanosheets.

[0010] (3) Add the modified MXene nanosheets and poly-lysine obtained in step (2) into a reaction bottle containing 30 mL of deionized water, add 2-4 mL of acetic acid, then add acetone aldehyde and formaldehyde, react at 80° C. for 2-3 h, wash with deionized water three times, and freeze-dry to obtain a MXene nanosheet / poly-lysine composite material;

[0011] (4) Add ammonium cerium nitrate to 30 mL of N,N-dimethylformamide, stir for 10 min, add terephthalic acid, add 1 mL of formic acid, place in a reactor, react at 100 ° C for 10-12 h, take the precipitate, wash it clean, and vacuum dry it at 60 ° C for 10 h to obtain Ce-MOF;

[0012] (5) Take the Ce-MOF obtained in step (4) and add it to 30 mL of N,N-dimethylformamide, and ultrasonically treat it for 10-20 min. Then add the MXene nanosheet / poly-lysine composite material obtained in step (3) and ultrasonically treat it for 30-40 min. Then stir it at room temperature for 10-12 h. Take the precipitate, wash it with deionized water for 3 times, and vacuum dry it at 60°C for 10 h to obtain an antibacterial and anticorrosive nanocomposite material.

[0013] Furthermore, in step (1), the mass ratio of LiF to Ti3AlC2 is 1:1-1.5.

[0014] Furthermore, in step (1), the concentration of the HCl solution is 9 mol / L, the power of the ultrasonic treatment is 400 W, and the speed of the centrifuge is 4000 r / min.

[0015] Furthermore, in step (2), the volume ratio of ethanol to water in the ethanol aqueous solution is 1:9, and the power of ultrasonic treatment is 400W.

[0016] Furthermore, in step (3), the mass ratio of the modified MXene nanosheets to poly-lysine is 1:1-1.5, and the volume ratio of methylglyoxal to formaldehyde is 2-3:1.

[0017] Furthermore, in step (4), the mass ratio of the ammonium cerium nitrate to terephthalic acid is 5:1-2.

[0018] Furthermore, in step (5), the mass ratio of the Ce-MOF to the MXene nanosheet / poly-lysine composite material is 1-2:1, and the power of the ultrasonic treatment is 400W.

[0019] Furthermore, the dispersant is hydroxypropyl methylcellulose, the defoaming agent is an organosilicon defoaming agent, the leveling agent is a polyether-modified organosiloxane, the thickener is a polyurethane thickener, and the film-forming aid is propylene glycol butyl ether.

[0020] The present invention provides a method for preparing a multifunctional environmentally friendly coating, which specifically comprises the following steps:

[0021] Take water-based polyurethane resin and add it to deionized water, add antibacterial and anticorrosive nanocomposite materials, stir for 10 minutes, add dispersant, defoamer, leveling agent and thickener, stir for 20 minutes, add film-forming aid, stir for 5 minutes, and obtain a multifunctional environmentally friendly coating.

[0022] The beneficial effects achieved by the present invention are as follows:

[0023] The present invention uses (3-aminopropyl) triethoxysilane to modify MXene nanosheets, and then grafts polylysine to prepare a MXene nanosheet / polylysine composite material. At the same time, Ce-MOF is composited to obtain an antibacterial and anticorrosive nanocomposite material. The antibacterial and anticorrosive nanocomposite material is added to the coating to effectively fill the defects in the coating, thereby reducing the porosity of the coating and improving the strength and corrosion resistance of the coating. The MXene nanosheets have excellent mechanical properties and rich surface groups. The layered structure of the MXene material can reduce the movement speed of the corrosive medium in the coating and improve the corrosion resistance of the coating. By grafting polylysine on the MXene nanosheets, the antibacterial and anticorrosive nanocomposite material can effectively fill the defects in the coating and reduce the porosity of the coating. Polylysine can avoid the accumulation and aggregation of MXene nanosheets due to the presence of hydrogen bonds and van der Waals interactions between layers, and improve the dispersibility of MXene nanosheets. MXene nanosheets modified with (3-aminopropyl)triethoxysilane are then grafted with polylysine. Polylysine can increase the loading amount with the help of the layered structure of MXene materials, and give full play to the antibacterial effect of polylysine. Ce-MOF can form a stable combination with MXene nanosheets through surface hydroxyl groups, etc., to improve the stability of MXene nanosheets. The cerium ions in Ce-MOF can generate OH in the cathode area. -A reaction occurs to generate precipitation, which reduces the corrosion current in the cathode area. The formed precipitate has higher corrosion resistance and slows down the corrosion of the substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The thermal stability test results of the multifunctional environmentally friendly coatings of Examples 1-3 and Comparative Examples 1-2 of the present invention are shown in FIG.

[0025] Figure 2 The test results of the antibacterial effect of the multifunctional environmentally friendly coatings of Examples 1-3 and Comparative Examples 1-2 of the present invention are shown;

[0026] Figure 3 Scanning electron microscope image of the antibacterial and anticorrosive nanocomposite material prepared in Example 1 of the present invention;

[0027] Figure 4 This is a surface image of an iron component coated with the multifunctional environmentally friendly coating prepared in Example 1 of the present invention.

[0028] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0031] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0032] The sources of some materials in the examples are as follows:

[0033] Waterborne polyurethane resin was purchased from Shandong Liang New Material Technology Co., Ltd.;

[0034] The dispersant was hydroxypropyl methylcellulose, purchased from Anhui Youtai Bioengineering Co., Ltd.;

[0035] The defoamer was an organosilicon defoamer, model BYK-065, purchased from BYK Chemicals, Germany;

[0036] The leveling agent is polyether-modified organosiloxane, model S-301, purchased from Guangzhou Yihua Digital Technology Co., Ltd.;

[0037] The thickener was a polyurethane thickener, model PU-16, purchased from Qingdao Enze Chemical Co., Ltd.;

[0038] The film-forming aid was propylene glycol butyl ether, CAS No.: 5131-66-8, purchased from Aladdin Biochemical Technology Co., Ltd.

[0039] Example 1

[0040] A multifunctional environmentally friendly coating comprises the following components in parts by weight: 50 parts of waterborne polyurethane resin, 8 parts of antibacterial and anticorrosive nanocomposite materials, 2 parts of dispersant, 2 parts of defoamer, 2 parts of leveling agent, 2 parts of thickener, 1 part of film-forming aid and 15 parts of deionized water.

[0041] Furthermore, the preparation method of the antibacterial and anticorrosive nanocomposite material comprises the following steps:

[0042] (1) Disperse 1 g LiF in 50 mL HCl solution with a concentration of 9 mol / L, add 1 g Ti3AlC2, and react at 35 °C with stirring for 24 h. After reaction, wash with deionized water until neutral, ultrasonically treat for 40 min at a power of 400 W, centrifuge for 1 h at a speed of 4000 r / min, and dry the centrifuged product in an oven at 40 °C for 10 h to obtain MXene nanosheets.

[0043] (2) Take 1 g of the MXene nanosheet obtained in step (1) and add it to a container containing 30 mL of ethanol aqueous solution, where the volume ratio of ethanol to water in the ethanol aqueous solution is 1:9, and ultrasonically treat for 30 min at a power of 400 W. Then, add 2 mL of triethylamine dropwise and stir at room temperature for 3 h. Then, take 2 mL of (3-aminopropyl)triethoxysilane and dissolve it in 10 mL of ethanol, add it to the above container, react at 60 ° C for 8 h, wash it with deionized water three times, and vacuum dry it at 60 ° C for 10 h to obtain modified MXene nanosheets.

[0044] (3) Take 1 g of the modified MXene nanosheets obtained in step (2) and 1 g of poly-lysine and add them to a reaction bottle containing 30 mL of deionized water, add 2 mL of acetic acid, then add 2 mL of acetone aldehyde and 1 mL of formaldehyde, react at 80 ° C for 2 h, wash with deionized water three times, and freeze-dry to obtain a MXene nanosheet / poly-lysine composite material;

[0045] (4) Take 0.5 g of ammonium cerium nitrate and add it to 30 mL of N,N-dimethylformamide, stir for 10 min, add 0.1 g of terephthalic acid, add 1 mL of formic acid, place in a reactor, react at 100 ° C for 10 h, take the precipitate, wash it clean, and vacuum dry it at 60 ° C for 10 h to obtain Ce-MOF;

[0046] (5) Take 1 g of Ce-MOF obtained in step (4), add it into 30 mL of N,N-dimethylformamide, and ultrasonically treat it for 10 min at a power of 400 W. Add 1 g of MXene nanosheets / poly-lysine composite material obtained in step (3), and ultrasonically treat it for 30 min at a power of 400 W. Then stir at room temperature for 10 h. Take the precipitate, wash it with deionized water for 3 times, and vacuum dry it at 60 ° C for 10 h to obtain an antibacterial and anticorrosive nanocomposite material.

[0047] This embodiment provides a method for preparing a multifunctional environmentally friendly coating, which specifically includes the following steps:

[0048] Add waterborne polyurethane resin and antibacterial and anticorrosive nanocomposite materials into deionized water and stir for 10 minutes. Add dispersant, defoamer, leveling agent and thickener and stir for 20 minutes. Add film-forming aid and stir for 5 minutes to obtain a multifunctional environmentally friendly coating.

[0049] Example 2

[0050] A multifunctional environmentally friendly coating comprises the following components in parts by weight: 60 parts of waterborne polyurethane resin, 12 parts of antibacterial and anticorrosive nanocomposite materials, 5 parts of dispersant, 4 parts of defoaming agent, 4 parts of leveling agent, 4 parts of thickener, 3 parts of film-forming aid and 25 parts of deionized water.

[0051] Furthermore, the preparation method of the antibacterial and anticorrosive nanocomposite material comprises the following steps:

[0052] (1) Disperse 1 g LiF in 50 mL HCl solution with a concentration of 9 mol / L, add 1.5 g Ti3AlC2, and react at 35 °C with stirring for 24 h. After reaction, wash with deionized water until neutral, ultrasonically treat for 60 min at a power of 400 W, centrifuge for 2 h at a speed of 4000 r / min, and dry the centrifuged product in an oven at 40 °C for 12 h to obtain MXene nanosheets.

[0053] (2) Take 2 g of the MXene nanosheets obtained in step (1) and add them to a container containing 30 mL of ethanol aqueous solution, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 1:9, and ultrasonically treat for 30 min at a power of 400 W. Then, add 3 mL of triethylamine dropwise and stir at room temperature for 4 h. Then, take 3 mL of (3-aminopropyl)triethoxysilane and dissolve it in 10 mL of ethanol, add it to the above container, react at 60 ° C for 8 h, wash it with deionized water three times, and vacuum dry it at 60 ° C for 10 h to obtain modified MXene nanosheets.

[0054] (3) Take 1 g of the modified MXene nanosheets obtained in step (2) and 1.5 g of poly-lysine and add them to a reaction bottle containing 30 mL of deionized water, add 4 mL of acetic acid, then add 3 mL of acetone aldehyde and 1 mL of formaldehyde, react at 80 ° C for 3 h, wash with deionized water three times, and freeze-dry to obtain a MXene nanosheet / poly-lysine composite material;

[0055] (4) Take 0.5 g of ammonium cerium nitrate and add it to 30 mL of N,N-dimethylformamide, stir for 10 min, add 0.2 g of terephthalic acid, add 1 mL of formic acid, place in a reactor, react at 100 ° C for 12 h, take the precipitate, wash it clean, and vacuum dry it at 60 ° C for 10 h to obtain Ce-MOF;

[0056] (5) Take 2 g of Ce-MOF obtained in step (4), add it into 30 mL of N,N-dimethylformamide, and ultrasonically treat it for 20 min at a power of 400 W. Then add 1 g of MXene nanosheets / poly-lysine composite material obtained in step (3), and ultrasonically treat it for 40 min at a power of 400 W. Then stir at room temperature for 12 h. Take the precipitate, wash it with deionized water for 3 times, and vacuum dry it at 60 ° C for 10 h to obtain an antibacterial and anticorrosive nanocomposite material.

[0057] This embodiment provides a method for preparing a multifunctional environmentally friendly coating, and the preparation method is implemented with reference to Example 1.

[0058] Example 3

[0059] A multifunctional environmentally friendly coating comprises the following components in parts by weight: 55 parts of waterborne polyurethane resin, 10 parts of antibacterial and anticorrosive nanocomposite materials, 4 parts of dispersant, 3 parts of defoaming agent, 3 parts of leveling agent, 3 parts of thickener, 2 parts of film-forming aid and 20 parts of deionized water.

[0060] Furthermore, the preparation method of the antibacterial and anticorrosive nanocomposite material comprises the following steps:

[0061] (1) Disperse 1 g LiF in 50 mL HCl solution with a concentration of 9 mol / L, add 1.3 g Ti3AlC2, and react at 35 °C with stirring for 24 h. After reaction, wash with deionized water until neutral, ultrasonically treat for 50 min at a power of 400 W, centrifuge for 1.5 h at a speed of 4000 r / min, and dry the centrifuged product in an oven at 40 °C for 11 h to obtain MXene nanosheets.

[0062] (2) 1.5 g of the MXene nanosheet obtained in step (1) was added to a container containing 30 mL of ethanol aqueous solution, wherein the volume ratio of ethanol to water in the ethanol aqueous solution was 1:9, and ultrasonic treatment was performed for 30 min at a power of 400 W. 2.5 mL of triethylamine was added dropwise, and the mixture was stirred at room temperature for 3.5 h. Then 2.5 mL of (3-aminopropyl)triethoxysilane was dissolved in 10 mL of ethanol and added to the above container. The mixture was reacted at 60 ° C for 8 h, washed with deionized water three times, and vacuum dried at 60 ° C for 10 h to obtain modified MXene nanosheets.

[0063] (3) Take 1 g of the modified MXene nanosheets obtained in step (2) and 1.3 g of poly-lysine and add them to a reaction bottle containing 30 mL of deionized water, add 3 mL of acetic acid, then add 2.5 mL of acetone aldehyde and 1 mL of formaldehyde, react at 80 ° C for 2.5 h, wash with deionized water three times, and freeze-dry to obtain a MXene nanosheet / poly-lysine composite material;

[0064] (4) Take 0.5 g of ammonium cerium nitrate and add it to 30 mL of N,N-dimethylformamide, stir for 10 min, add 0.15 g of terephthalic acid, add 1 mL of formic acid, place in a reactor, react at 100 ° C for 11 h, take the precipitate, wash it clean, and vacuum dry it at 60 ° C for 10 h to obtain Ce-MOF;

[0065] (5) Take 1.5 g of the Ce-MOF obtained in step (4), add it to 30 mL of N,N-dimethylformamide, and ultrasonically treat it for 15 min at a power of 400 W. Add 1 g of the MXene nanosheet / poly-lysine composite material obtained in step (3), and ultrasonically treat it for 35 min at a power of 400 W. Then stir at room temperature for 11 h. Take the precipitate, wash it with deionized water three times, and vacuum dry it at 60 ° C for 10 h to obtain an antibacterial and anticorrosive nanocomposite material.

[0066] This embodiment provides a method for preparing a multifunctional environmentally friendly coating, and the preparation method is implemented with reference to Example 1.

[0067] Comparative Example 1

[0068] This comparative example provides a multifunctional environmentally friendly coating and a preparation method thereof. The difference between it and Example 1 is that the antibacterial and anticorrosive nanocomposite material does not contain MXene nanosheets / polylysine composite material, and the other components and component contents are the same as those in Example 1.

[0069] Comparative Example 2

[0070] This comparative example provides a multifunctional environmentally friendly coating and a preparation method thereof. The difference between the comparative example and Example 1 is that the antibacterial and anticorrosive nanocomposite material does not contain Ce-MOF, and the other components and component contents are the same as those in Example 1.

[0071] Experimental example

[0072] The coatings prepared in Examples 1-3 and Comparative Examples 1 and 2 were coated on flat iron parts under the same conditions, cured at 150° C. for 25 min, the flatness and gloss of the coatings were observed, and then performance tests were performed.

[0073] 1. The hardness of the multifunctional environmentally friendly coatings prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2 was tested. The hardness was measured by the pencil method according to GB / T 6739. The test results are shown in Table 1.

[0074] Table 1 Hardness test results

[0075]

[0076] 2. The corrosion resistance of the multifunctional environmentally friendly coatings prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2 was tested. The specific method is as follows: Referring to GB / T 1763 standard, salt water resistance, acid resistance and alkali resistance were tested, the time and sample changes were recorded, and discoloration, blistering, wrinkling, shedding and rusting were evaluated. The test data are shown in Table 2.

[0077] Table 2 Corrosion resistance test results

[0078]

[0079] 3. The multifunctional environmentally friendly coatings prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2 were subjected to a thermal stability test. The specific method is as follows: a thermogravimetric analyzer was used to increase the temperature from 20°C to 700°C in a nitrogen atmosphere at a heating rate of 20°C / min, and T 5% (temperature at which mass loss is 5%) and T 90% (Temperature at which mass loss is 90%).

[0080] 4. The antibacterial effect of the multifunctional environmentally friendly coatings prepared in Examples 1-3 and Comparative Examples 1 and 2 of the present invention was tested. The specific method is as follows: Referring to GB / T 21866-2008 standard, the coating plate and the blank plate were placed in culture dishes respectively, 0.5 mL of the prepared bacterial suspension was dripped onto the surface of the coating plate respectively, and a PE film was covered thereon to make the bacterial liquid evenly contact the surface to be tested, and the plate was placed in an incubator, and cultured for 24 hours at a temperature of 37° C. and a relative humidity of greater than 90%. The culture dish was taken out, and the PE film and the sample surface were repeatedly washed with deionized water. 1 mL of the washing solution after gradient dilution was dripped into another culture dish, and a solid culture medium was poured into it and shaken horizontally. After it was completely cooled, it was inverted and placed in an incubator. After culturing at 37° C. for 48 hours, the colonies on the plate were counted, and the antibacterial rate of the coating was calculated according to the following formula:

[0081] R=(BC) / B×100%

[0082] Where: R is the antibacterial rate (%), B is the number of colonies recovered on the blank plate after 24 hours (cfu / mL), and C is the number of colonies recovered on the coating plate after 24 hours (cfu / mL).

[0083] 5. The surface morphology of the antibacterial and anticorrosive nanocomposite material described in Example 1 was observed using a scanning electron microscope.

[0084] Results Analysis

[0085] Table 1 shows the hardness test results of the multifunctional environmentally friendly coatings of Examples 1-3 and Comparative Examples 1-2 of the present invention. It can be seen from the data in Table 1 that compared with Comparative Examples 1 and 2, Example 1 has a higher hardness.

[0086] Table 2 shows the corrosion resistance test results of the multifunctional environmentally friendly coatings of Examples 1-3 and Comparative Examples 1-2 of the present invention. Comparative Example 1 has better corrosion resistance than Comparative Example 1. This is because the layered structure of the MXene material can reduce the movement speed of the corrosive medium in the coating and improve the corrosion resistance of the coating. Example 1 has better corrosion resistance than Comparative Example 2. This is because the cerium ions in Ce-MOF can generate OH in the cathode area. - A reaction occurs to generate precipitation, which reduces the corrosion current in the cathode area. The formed precipitate has higher corrosion resistance and slows down the corrosion of the substrate.

[0087] Figure 1 The thermal stability test results of the multifunctional environmentally friendly coatings of Examples 1-3 and Comparative Examples 1-2 of the present invention are shown in the figure. As shown in the figure, the T 5% The T of Comparative Example 1 is 223℃, 221℃, and 224℃ respectively. 5% is 161°C, and the T 5%is 186°C, and the T 90% The T of Comparative Example 1 is 577℃, 569℃, and 573℃ respectively. 90% is 461°C, and the T 5% It is 476℃.

[0088] Figure 2 This is a graph showing the antibacterial effect test results of the multifunctional environmentally friendly coatings of Examples 1-3 of the present invention and Comparative Examples 1-2. As shown in the figure, the antibacterial rates of Escherichia coli of Examples 1-3 are 99.3%, 98.9% and 99.1%, respectively, that of Comparative Example 1 is 85.4%, and that of Comparative Example 2 is 91.2%. The antibacterial rates of Staphylococcus aureus of Examples 1-3 are 99.5%, 99.2% and 99.4%, respectively, that of Comparative Example 1 is 86.2%, and that of Comparative Example 2 is 91.8%. There is a significant improvement over Example 1 and Comparative Example 1. This is due to the composite of polylysine and MXene nanosheets, which can fully exert the antibacterial effect of polylysine with the help of the layered structure of the MXene material.

[0089] Figure 3 This is a scanning electron microscope image of the antibacterial and anticorrosive nanocomposite material prepared in Example 1 of the present invention.

[0090] Figure 4 This is a surface image of an iron component coated with the multifunctional environmentally friendly coating prepared in Example 1 of the present invention. It can be seen that the coating has good flatness and glossiness.

[0091] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0092] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A multifunctional environmentally friendly coating, characterized in that: The invention comprises the following components in parts by weight: 50-60 parts of waterborne polyurethane resin, 8-12 parts of antibacterial and anticorrosive nanocomposite materials, 2-5 parts of dispersant, 2-4 parts of defoamer, 2-4 parts of leveling agent, 2-4 parts of thickener, 1-3 parts of film-forming aid, and 15-25 parts of deionized water; The preparation method of the antibacterial and anticorrosive nanocomposite material comprises the following steps: (1) Disperse LiF in 50 mL of HCl solution, add Ti3AlC2, and react at 35 °C with stirring for 24 h. After reaction, wash with deionized water until neutral, ultrasonicate for 40-60 min, centrifuge for 1-2 h, and dry the centrifuged product in an oven at 40 °C for 10-12 h to obtain MXene nanosheets. (2) 1-2 g of the MXene nanosheet obtained in step (1) was added to a container containing 30 mL of ethanol aqueous solution, and ultrasonically treated for 30 min. 2-3 mL of triethylamine was added dropwise, and stirred at room temperature for 3-4 h. Then 2-3 mL of (3-aminopropyl)triethoxysilane was dissolved in 10 mL of ethanol and added to the above container. The mixture was reacted at 60 ° C for 8 h, washed with deionized water for 3 times, and vacuum dried at 60 ° C for 10 h to obtain modified MXene nanosheets. (3) Add the modified MXene nanosheets and poly-lysine obtained in step (2) into a reaction bottle containing 30 mL of deionized water, add 2-4 mL of acetic acid, then add acetone aldehyde and formaldehyde, react at 80° C. for 2-3 h, wash with deionized water three times, and freeze-dry to obtain a MXene nanosheet / poly-lysine composite material; (4) Add ammonium cerium nitrate to 30 mL of N,N-dimethylformamide, stir for 10 min, add terephthalic acid, add 1 mL of formic acid, place in a reactor, react at 100 ° C for 10-12 h, take the precipitate, wash it clean, and vacuum dry it at 60 ° C for 10 h to obtain Ce-MOF; (5) Take the Ce-MOF obtained in step (4) and add it to 30 mL of N,N-dimethylformamide, and ultrasonically treat it for 10-20 min. Then add the MXene nanosheet / poly-lysine composite material obtained in step (3) and ultrasonically treat it for 30-40 min. Then stir it at room temperature for 10-12 h. Take the precipitate, wash it with deionized water for 3 times, and vacuum dry it at 60°C for 10 h to obtain an antibacterial and anticorrosive nanocomposite material.

2. A method for preparing the multifunctional environmentally friendly coating according to claim 1, characterized in that: The specific steps include: Take water-based polyurethane resin and add it to deionized water, add antibacterial and anticorrosive nanocomposite materials, stir for 10 minutes, add dispersant, defoamer, leveling agent and thickener, stir for 20 minutes, add film-forming aid, stir for 5 minutes, and obtain a multifunctional environmentally friendly coating.

3. The method for preparing the multifunctional environmentally friendly coating according to claim 2, characterized in that: In step (1), the mass ratio of LiF to Ti3AlC2 is 1:1-1.

5.

4. The method for preparing the multifunctional environmentally friendly coating according to claim 3, characterized in that: In step (1), the concentration of the HCl solution is 9 mol / L; the power of the ultrasonic treatment is 400 W; and the speed of the centrifuge is 4000 r / min.

5. The method for preparing the multifunctional environmentally friendly coating according to claim 4, characterized in that: In step (2), the volume ratio of ethanol to water in the ethanol aqueous solution is 1:9; and the power of ultrasonic treatment is 400W.

6. The method for preparing the multifunctional environmentally friendly coating according to claim 5, characterized in that: In step (3), the mass ratio of the modified MXene nanosheets to poly-lysine is 1:1-1.5, and the volume ratio of methylglyoxal to formaldehyde is 2-3:

1.

7. The method for preparing the multifunctional environmentally friendly coating according to claim 6, characterized in that: In step (4), the mass ratio of the ammonium cerium nitrate to terephthalic acid is 5:1-2.

8. The method for preparing the multifunctional environmentally friendly coating according to claim 7, characterized in that: In step (5), the mass ratio of the Ce-MOF to the MXene nanosheet / poly-lysine composite material is 1-2:1, and the power of the ultrasonic treatment is 400W.

9. The method for preparing the multifunctional environmentally friendly coating according to claim 8, characterized in that: The dispersant is hydroxypropyl methylcellulose, the defoamer is an organosilicon defoamer, the leveling agent is a polyether-modified organosiloxane, the thickener is a polyurethane thickener, and the film-forming aid is propylene glycol butyl ether.

Citation Information

Patent Citations

  • Nano-silver loaded graphene antibacterial agent and graphene in-situ reduction nano-silver loaded water-based antibacterial coating

    CN107815193A